2011
DOI: 10.1212/wnl.0b013e31822c623b
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvascular changes and subsequent vascular events after ischemic stroke

Abstract: Retinal microvascular changes predicted subsequent vascular events after ischemic stroke, independent of traditional risk factors and stroke subtype. Thus, retinal imaging has a potential role in predicting the risk of recurrent vascular events after ischemic stroke and in understanding novel vascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
0
33
1
Order By: Relevance
“…Furthermore, alterations in conjunctival blood flow due to ICA occlusion have also been reported (Pavlou and Wolff, 1959). Recently, several studies have demonstrated retinal microvascular changes to be associated with, or predictive of stroke (De Silva et al, 2011; Doubal et al, 2009; Ikram et al, 2006; McGeechan et al, 2009; Ong et al, 2013; Wang et al, 2007; Wieberdink et al, 2010; Wong et al, 2001). Since the retina and conjunctiva have a common source of blood from the ophthalmic artery and analogous alterations in the retinal and conjunctival microvasculature have been reported in hypertension and diabetes (To et al, 2013; To et al, 2011), it is likely that the conjunctival microcirculation is also affected by stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, alterations in conjunctival blood flow due to ICA occlusion have also been reported (Pavlou and Wolff, 1959). Recently, several studies have demonstrated retinal microvascular changes to be associated with, or predictive of stroke (De Silva et al, 2011; Doubal et al, 2009; Ikram et al, 2006; McGeechan et al, 2009; Ong et al, 2013; Wang et al, 2007; Wieberdink et al, 2010; Wong et al, 2001). Since the retina and conjunctiva have a common source of blood from the ophthalmic artery and analogous alterations in the retinal and conjunctival microvasculature have been reported in hypertension and diabetes (To et al, 2013; To et al, 2011), it is likely that the conjunctival microcirculation is also affected by stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all of the factors described above additionally influence the microcirculation and contribute to intraglomerular pressure. [10][11][12][13][14][15][16] Thus, it is not surprising that renal microvascular pathology has been considered an important factor in CKD progression. 17 One pathophysiological aspect of the microcirculation is vascular remodeling in small arteries, including microvascular narrowing.…”
mentioning
confidence: 99%
“…Retina offers a unique window to the study of cerebral micro vascular lesion, because of its accessibility and non-invasiveness through fundoscopy. Several studies [18][19][20] report that retinal micro vascular changes such as arteriolar narrowing, arteriovenous nicking, micro aneurysms, micro exudates and micro hemorrhages are strongly associated with subclinical [21][22][23][24] and clinical cerebrovascular damage. Agreeing with those reports, we found in our patient, several lesions, indicating an important degree of retinal small vessels injury associated with important silent cerebrovascular injuries observed on MRI.…”
Section: Discussionmentioning
confidence: 99%